Is there any relationship between serum γ-glutamyltransferase levels and premature coronary artery disease? - Özlü, Mehmet Fatih; Ayhan, Suzi Selim; Erdem, Alim; Tosun, Mehmet; Öztürk, Serkan; Erdem, Kemalettin; Özyașar, Mehmet; Dönmez, Ibrahim; Alcelik, Aytekin; Yazıc, Mehmet (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Background: The relationship between γ-glutamyltransferase (GGT) and coronary artery disease (CAD) has been revealed in several previous studies. However, the relationship between the severity of CAD and GGT levels has not been previously studied in a premature group (< 40 years old). Aim : We aim to investigate whether GGT is associated with premature CAD. Material and methods: The study population consisted of 181 premature coronary artery disease patients (group 1; mean age: 36.5 ±2.5 years) and 80 controls (group 2; mean age: 37.2 ±2.3 years). The severity of CAD in group 1 was evaluated by the Gensini scoring system. γ-Glutamyltransferase levels and the other basic biochemical parameters were analyzed, and relations with severity of CAD were evaluated. Results: There were no statistically significant differences in serum GGT activity between the two groups (p > 0.05). γ-Glutamyltransferase levels in group 1 were found not to be correlated with the severity of premature CAD (r = –0.016, p = 0.828). Furthermore, in subgroup analyses we found glycated hemoglobin (HbA1c) levels significantly correlated with the severity of CAD in diabetic premature CAD patients, but not GGT (r = 0.448, p < 0.001; r = 0.157, p = 0.127, respectively). Conclusions: γ-Glutamyltransferase level was not associated with severity of CAD in the premature group. Possibly, there is no predictive importance of GGT in patients with premature CAD.